Rekomendasi Pembuatan Roda Berbahan Dasar Polyurethane Menggunakan Metode Simple Additive Weighting (SAW) Studi Kasus Pada CV. Sumber Rejeki Teknik - Muhammad Vidi Mycharoka; Nurul Hidayat; Tri Afirianto (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2019)
In the world of industry the application of Polyurethane wheels are commonly used for factory and warehouse. At CV. Sumber Rejeki Teknik is a manufacturer of Polyurethane based wheels that focuses on making wheels for forklifts and trolleys. In manufacturing Polyurethane wheels, CV. Sumber Rejeki Teknik uses several Polyurthane materials because with a number of different material variations and characteristics, it is necessary to look for the best material for making Polyurethane wheels with the appropriate preferences and at low prices. Use the Simple Additive Weighting Method to find recommendations for the best material with a ranking form, the results of the agreement using the Simple Additive Weighting method then evaluating it using the Spearman Rank Correlation and Rank Correlation method. The results obtained based on the testing showed that the accuracy for forklifts was 58.333% and for trolleys was 41,666%. In testing carried out using Spearman Rank Correlaton the results for forklifts were 0.21678 and for trolleys were 0.24475.